Environmental Education: Reflecting on Application of Environmental Attitudes Measuring Scale in Higher Education Students - Helen Kopnina; Andreea Cocis (MDPI AG, 2017)
The Ecocentric and Anthropocentric Attitudes toward the Sustainable Development (EAATSD) scale measures environmental concern in relation to sustainable development. This article will discuss how this scale was tested with three groups of Dutch higher education students. Findings demonstrate that anthropocentric and ecocentric values are independent of the students' chosen course of study, suggesting that students attracted by the 'sustainable development' course title do not necessarily associate 'sustainability' with ecocentric aims. This article discusses why ecocentric values are beneficial to the objective of a sustainable society and proposes ways forward in which these values can be enhanced in learners.